Finance and Development, June 1974. (Finance and Development; Finance and Development, 1974)
This paper describes the technical improvement in developing countries. It highlights that developing countries have relied heavily for their industrial development upon foreign enterprises as sources of technology and management systems. The paper underscores that through direct investment or under licensing arrangements, foreign corporations have supplied a vast array of industrial products and equipment and have exercised a major role in the design and construction of processing and manufacturing facilities in newly industrializing countries.